Women Safety Night Patrolling Robot Using IOT - M Renu Babu; B Hari Krishna; G Rakesh; M Sai Tejashri; Y Parichitha (International Journal of Engineering and Management Research, 2021)
India's greatest threat is the safety of its women. Women do not feel safe in a variety of situations. This needs to be addressed as quickly as feasible. Technology evolves and develops on a daily basis, affecting how people live. As a result, the focus of this article is on modernising the technological framework in order to strengthen women's safety mechanisms. We introduce a new security method in this study to protect women during unusual behaviours. A new security technique based on a patrolling robot using the Raspberry Pi has been proposed. In this case, a night vision camera can be employed to secure any location. Various machine learning methods are applied to improve the classifier's accuracy. The findings suggest that the suggested method outperforms existing methods.